ZNF169 promotes thyroid cancer progression via upregulating FBXW10 - Wen Luo; Qiyu Xiao; Ying Fu (Cell Division)
Abstract Background Zinc finger protein 169 (ZNF169) plays a key role in cancer development. However, the specific role of ZNF169 in the tumorigenesis of thyroid carcinoma (THCA) remains poorly understood. Methods The expression of ZNF169 was measured using immunohistochemistry, RT-qPCR, and western blot. Cell proliferation was detected using CCK-8 assay and cell colony formation assays, while cell migration was determined by Transwell assay. Flow cytometry was used to detect cell apoptosis and cell cycle distribution. The interaction of ZNF169 and its downstream gene was studied using luciferase assay and CHIP-PCR. Recovery assay in cells and animals were also performed to demonstrate the mechanism. Results ZNF169 was highly expressed in THCA tissues and cells lines compared with matched adjacent non-cancerous thyroid tissues or normal thyroid epithelial cell. Moreover, thyroid cancer cell proliferation and migration were suppressed following ZNF169 knockdown, while were potentiated by ZNF169 overexpression. ZNF169 also regulate THCA cell apoptosis and cell cycle progression. Mechanically, ZNF169 enhanced the transcription activity and expression of F-box/WD repeat-containing protein 10 (FBXW10) via the binding to its promoter. There was a positive correlation between ZNF169 and FBXW10 in THCA patients. In addition, knockdown of FBXW10 suppressed the proliferation of THCA cells. Recovery assays in vitro and in vivo demonstrated that FBXW10 knockdown reversed the effects of ZNF169 overexpression on THCA cell proliferation and tumor growth. Conclusions In summary, ZNF169 promotes THCA progression via upregulation of FBXW10, which may provide a novel theoretical basis for the development of clinical therapies for THCA.